2016
DOI: 10.5194/hess-20-1681-2016
|View full text |Cite
|
Sign up to set email alerts
|

Trends and abrupt changes in 104 years of ice cover and water temperature in a dimictic lake in response to air temperature, wind speed, and water clarity drivers

Abstract: Abstract. The one-dimensional hydrodynamic ice model, DYRESM-WQ-I, was modified to simulate ice cover and thermal structure of dimictic Lake Mendota, Wisconsin, USA, over a continuous 104-year period (1911-2014). The model results were then used to examine the drivers of changes in ice cover and water temperature, focusing on the responses to shifts in air temperature, wind speed, and water clarity at multiyear timescales. Observations of the drivers include a change in the trend of warming air temperatures fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 97 publications
3
50
0
Order By: Relevance
“…Changes in the remaining elements of the hydrological regime of Morskie Oko are in accordance with the majority of studies on lakes in various parts of the world, both in reference to thermal conditions (Adrian et al, 2009;Coats et al, 2006;Hampton et al, 2008) and the course of ice phenomena (Benson et al, 2012;Futter, 2003;Korhonen, 2006;Magee et al, 2016). The scale of transformations depends on the location and local conditions of particular lakes.…”
Section: Discussionsupporting
confidence: 50%
“…Changes in the remaining elements of the hydrological regime of Morskie Oko are in accordance with the majority of studies on lakes in various parts of the world, both in reference to thermal conditions (Adrian et al, 2009;Coats et al, 2006;Hampton et al, 2008) and the course of ice phenomena (Benson et al, 2012;Futter, 2003;Korhonen, 2006;Magee et al, 2016). The scale of transformations depends on the location and local conditions of particular lakes.…”
Section: Discussionsupporting
confidence: 50%
“…In the case of Lake Lunz (Austria), Kainz et al [12] observed a reduction of duration of ice cover, and the average rate of the phenomenon amounted to 1.85 day·dec -1 . In research on Lake Mendota (USA), Magee et al [13] found that the development of ice cover occurred 9 days per century later, and its disintegration occurred 12.3 days per century earlier, resulting in a decrease in duration of ice cover (by 21.3 days per century). In research on 75 lakes on the Northern Hemisphere, Benson et al [14] determined later freezing of lakes (0.3-1.6 day·dec -1 ), earlier disappearance of ice (0.5-1.9 day·dec -1 ), and its shorter duration (0.7-4.3 day·dec -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This refers to water level fluctuations [1], ice phenomena [2], as well as water temperature [3]. In addition to the research trend concerning the assessment of long-term tendencies of changes in the hydrosphere in the times of global warming, numerous studies refer to the effect of types of macroscale circulation of the atmosphere on its different components.…”
Section: Introductionmentioning
confidence: 99%